Book Review of: Matteo Bortolini: A Joyfully Serious Man. The Life of Robert Bellah - Knoebl, Wolfgang (Serendipities. Journal for the Sociology and History of the Social Sciences, 2022)
Bortolini, Matteo (2021) A Joyfully Serious Man. The Life of Robert Bellah, Princeton & Oxford: Princeton University Press. 497 pp. ISBN: 978-0-691-20440-6 Price: 35,00 / £28.00